2022
DOI: 10.3389/fneur.2022.904293
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the mean of 24-h venous blood glucose and in-hospital mortality among patients with subarachnoid hemorrhage: A matched cohort study

Abstract: ObjectiveThe aim of this study was to explore the correlation between the mean of 24-h venous blood glucose (BG) and in-hospital mortality and all-cause mortality (ACM) in patients with subarachnoid hemorrhage (SAH).MethodsDetailed clinical information was acquired from the Medical Information Mart for Intensive IV (MIMIC-IV) database. The best cutoff value of mean BG was calculated using the X-tile program. Univariate and multivariate logistic regressive analyses were utilized to analyze the prognosis signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…However, the underlying mechanisms remain unclear. Some studies have suggested that elevated Lp(a) levels may contribute to the formation of thrombi and fibrin networks, thereby promoting the adhesion, invasion, and metastasis of cancer cells 16 . However, animal studies have shown that the protein hydrolysate of Lp(a) exhibits anti‐tumor properties both in vivo and in vitro 18,19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the underlying mechanisms remain unclear. Some studies have suggested that elevated Lp(a) levels may contribute to the formation of thrombi and fibrin networks, thereby promoting the adhesion, invasion, and metastasis of cancer cells 16 . However, animal studies have shown that the protein hydrolysate of Lp(a) exhibits anti‐tumor properties both in vivo and in vitro 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…Elevated Lp(a) levels have been linked to more aggressive forms of prostate 15 and colorectal cancers, 16 while no associations have been observed with breast cancer 17 . However, the underlying mechanisms remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Blood glucose (>7.22 mmol/L) is a two-category variable applied to the risk threshold with a predictive value. High glucose levels are frequently associated with vasospasm, secondary ischemia, and poor outcomes ( 2 , 21 , 22 ). Hyperglycemia might be expected in aSAH patients due to the transient stress reaction and an acute metabolic response ( 21 ).…”
Section: Discussionmentioning
confidence: 99%